(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2024)
The association between endometriosis and infertility is well established and treatment is challenging. It is a chronic and debilitating disease with multiple pathophysiologic mechanisms. Treatment involves both surgical/medical interventions and ART for those with infertility. Evidence on the ideal approach is inadequate and guidelines vary. The patient’s symptomatology, age, fertility desires and prior surgical interventions are important factors to consider. Fertility preservation is paramount. We present an interesting case of a nulliparous patient who over four years has had recurrent ovarian endometriosis, underwent four laparoscopic surgical/medical interventions, and ultimately achieved a natural conception. Case A 32-year-old female presented in 2019 with symptoms of endometriosis confirmed on pelvic ultrasound. Laparoscopy, the gold standard was performed and the histology confirmed endometriosis. Postoperatively, she was on medical management to control symptoms. However, seven months later, she presented with worsening symptoms despite being on Leuprolide and later Visanne. Ultrasound showed recurrent ovarian endometriosis and uterine fibroids. A Laparoscopic myomectomy, adhesiolysis, and excision of ovarian endometriosis were done. She was then on Visanne but 6 months later her symptoms returned. A scan showed recurrent left ovarian endometriosis and she underwent laparoscopic excision. Her symptoms improved. Two years later she presented with worsening symptoms. A repeat ultrasound scan showed ovarian endometriosis. With a desire to conceive, laparoscopic excision of endometriosis, Adhesiolysis, and chromopertubation were performed. She conceived spontaneously four months later and is currently in her second trimester. Conclusion Treatment for endometriosis is an enigma and has to be individualized. Shared decision-making is important and repeated surgical/medical interventions with fertility preservation are a plausible approach for those keen on child-bearing.